2011
DOI: 10.1093/jmt/48.4.486
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Music Therapy Intergenerational Program on Children and Older Adults' Intergenerational Interactions, Cross-Age Attitudes, and Older Adults' Psychosocial Well-Being

Abstract: The purpose of this study was to examine the effect of participation in a music-based intergenerational music program on cross-age interactions and cross-age attitudes of elementary-age children and older adults, and older adults' psychosocial well-being. Twenty-one children in the 4th grade volunteered to participate in the experimental (n = 12) or control (n = 9) group. Twenty-six older adults from a retirement living facility also volunteered to participate in the experimental (n = 14) or control (n = 12) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 105 publications
4
65
1
8
Order By: Relevance
“…Belgrave (2011) no efectuó un registro escrito de las sesiones, a la vez que Boswell (2012), Celdrán, Villar & Triadó (2012), Chippendale (2013), y Jarrott & Smith (2011) no llevaron a cabo registro de ningún tipo durante las reuniones de seguimiento.…”
Section: Resultsunclassified
“…Belgrave (2011) no efectuó un registro escrito de las sesiones, a la vez que Boswell (2012), Celdrán, Villar & Triadó (2012), Chippendale (2013), y Jarrott & Smith (2011) no llevaron a cabo registro de ningún tipo durante las reuniones de seguimiento.…”
Section: Resultsunclassified
“…In a non-randomised controlled study [6] explored the impacts of an intergenerational music programme between 26 older people from a retirement living facility and 21 children aged 9-10 on grade 4 at elementary school. This was a 10-session programme with each session lasting half an hour and consisting of singing, moving to music, structured communication and instrument playing.…”
Section: Resultsmentioning
confidence: 99%
“…The exact mechanisms of how these benefits could occur have not been very well documented. However, it was shown that the intergenerational activities performed with smaller groups or one to one pairs tended to show greater effects [5,6,10,18]. In this way children are more exposed to older people's accumulated knowledge and experiences and have an opportunity to learn about older people's views and wisdom.…”
Section: Discussionmentioning
confidence: 99%
“…Igualmente, estas relaciones e intercambios también presentan beneficios en las personas mayores. Las relaciones intergeneracionales tienen beneficios en el envejecimiento cognitivo (Whitehouse, 2013) y también derivan beneficios en el bienestar psicosocial (Belgrave, 2011). Murillo y Krichesky (2015), aluden a diferentes experiencias que contribuyen a fomentar mecanismos que propician el aprendizaje con la comunidad desde múltiples vertientes, éstas son: 1) aprender de la comunidad: invitar a familiares u otros agentes a que compartan su conocimiento o experiencia en el contexto educativo, 2) aprender con la comunidad: familias y maestros aprenden de manera conjunta sobre una temática (p.ej.…”
Section: ~ Différenciation Pédagogique Et Participation Démocratique unclassified
“…Sin embargo, en el proyecto de Betxí a lo largo del tiempo los abuelos son la principal fuente de información y su protagonismo en el mismo es notable. Para las personas mayores es muy gratificante, dar testimonio y compartir conocimiento, lo conciben como una responsabilidad (Belgrave, 2011;Whitehouse, 2013).…”
Section: ~ Valores Democráticosunclassified